PENGARUH SELF-EFFICACY DAN ADVERSITY QUOTIENT TERHADAP INTENSI BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN BISNIS UNIVERSITAS NEGERI SURABAYA - Septyan Budy Cahya; Farhan Rachmat Widianto (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Indonesia is one of the most populous countries in the world, yet it still faces serious challenges such as a high unemployment rate. One strategic solution to this issue is entrepreneurship. As future leaders, university students are expected to have a strong entrepreneurial intention. This study aims to analyze the influence of self-efficacy and adversity quotient on the entrepreneurial intention of students in the Business Education Program at Universitas Negeri Surabaya. This research uses a quantitative approach with a survey method through an online questionnaire. A total of 205 students participated, and the data were analyzed using IBM SPSS Statistics 25. The t-test results indicate that both self-efficacy and adversity quotient significantly influence entrepreneurial intention, with a value of 0.000 (<0.05). The F-test also confirms a simultaneous effect of both variables (F = 56.244; sig = 0.000). The coefficient of determination (R²) is 0.351, meaning that 35.1% of the variation in entrepreneurial intention is explained by self-efficacy and adversity quotient. These findings highlight that confidence in one's abilities and resilience in facing adversity are essential psychological factors that drive students' intentions to become entrepreneurs.